PELAKSANAAN KHIYAR SYARAT DALAM JUAL BELI DI PASAR SANGKUMPAL BONANG PADANGSIDIMPUAN DI TINJAU DARI KOMPILASI HUKUM EKONOMI SYARIAH - SOFIA SARI (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
This papers discussed about the implementation of the khiyar syarat, and review of Islamic law in implementing the khiyar syarat.  Then problems often occur in buying and selling activities, the clothes merchants do not want to return the buyer's money because there is no agreement between the seller and the buyer. This study aims to determine how the khiyar syarat are implemented in the sale at the Sagumpal Bonang Market in Padangsidimpuan. And to find out about the review of the Kompilasi Hukum Ekonomi Syariah (KHES), on the implementation of the Khiyar syarat in buying and selling at Sangkumpal Bonang Market in Padangsidimpuan. This research is field research using a sociological juridical approach. Sources of data are primary data and secondary data. The data were collected by instruments such interviews, observation and documentation. Moreover, the process of data analysis was classified into descriptive research, namely to find specific and realistic about the problem that is happening and express themselves in the form of symptoms in order to solve existing problems in implementing khiyar syarat. The practice of the khiyar syarat carried out by some clothing traders in the Sangkumpal Bonang Market in Padangsidimpuan namely if the goods do not match after the sale and purchase transaction, the buyer can return the item but is exchanged for other goods, but if there are no similar items the buyer redeem the goods but the item is in good condition. In Reviewing Islamic Law on the terms of conditions in the Sangkumpal Bonang Market in the vicinity of the meeting, it was not in accordance with the requirements, because non-resident clothing traders canceled buying and selling transactions and asked for refunds when found items that did not match the goods were known after buying and selling transactions.